O ator no teatro performativo: reflexões e procedimentos de treinamento - Nunes, Ana Flávia Felice (2017)
This research aims to investigate the “Perfornative Theater” actor, concept proposed by Josette Féral. From there, the reflection on the dramaturgical tendencies of this theater, from a specific understanding of the body, as a body border. For yhis I rely mainly on the concept of “subjective-body”, in the perspective of Renato Ferracini, and scenic-body, ando f the scenic presence as the ability to inhabit the “places in between”, proposed by Eleonora Fabião. From these reflection I propose possible training of perception and listening, providing na attentive spongy body, directly related to the environment, based on Cassiano Sydow and his Studies on “self-care” and “self-restlessness”.